Konsep Pemimpin Gereja Katolik Menurut Perspektif Anthony D’Souza dan Sumbangannya bagi Pemimpin Gereja di Indonesia - Nino, Yeremias; Fahik, Henderikus Ati (Perspektif, 2025)
This study examines the concept of leadership in the Catholic Church based on Anthony D’Souza’s perspective and its contribution to Church leaders in Indonesia today. The leaders referred to in this study are Catholic priests. Anthony D’Souza emphasizes that leaders in the Catholic Church are called to serve. A servant leader fully dedicates themselves to serving God and others. This study highlights several key issues in Church leadership. First, some leaders exhibit authoritarian tendencies, failing to adopt a servant attitude and instead abusing their power. Second, some leaders prioritize personal interests over their congregation, neglecting their pastoral responsibilities and failing to provide the necessary guidance and development. Third, some leaders lack administrative discipline, creating opportunities for corruption. Therefore, a deeper understanding of the concept of leadership in the Catholic Church is expected to foster greater awareness among leaders in carrying out their pastoral duties within the community. This study aims to explore Anthony D’Souza’s leadership concept and its relevance to Church leaders in Indonesia. The research employs a qualitative approach using a literature study, drawing from Anthony D’Souza’s works and other relevant literature on leadership in the Catholic Church. The findings indicate that, according to Anthony D’Souza, the essence of leadership in the Catholic Church is centered on three fundamental aspects: being a servant, a shepherd, and a steward.